Measuring the Level of Urbanization, Adoption of Urban Values: Case of Immigration to Denizli City - Çeliktürk, Tanzer (European Scientific Journal, ESJ, 2017)
In this study, the case of Denizli province where the urban transformation projects are taken for the solution of the problem of uneven urbanization will be discussed. Within the scope of the Denizli example, it will be tried to measure the extent to which the urban values of rural migrants migrate to the city. In other words, the level of social urbanization will be tried to be determined. For this purpose, questions were asked about urbanization and social urbanization for those who came to work from surrounding cities and Denizli countryside. Within the framework of the answers given, efforts will be made to determine how the degree of social urbanization has changed in the context immigrants. In this framework, urbanization process and social urbanization process of Turkey in the first stage will be briefly summarized. In the second part; The development of Denizli and the migration movement to Denizli will be briefly summarized and the social urbanization grades of immigrants in Denizli context will be discussed. In the context of urbanization and social urbanization analysis in Denizli City case, questions including basic indicators of economic and social aspects of urbanization - occupation, income level, solidarity, solidarity, cooperation, education, organization, information, methods of seeking rights, religious and political issues and family relations- are tailored and asked to participants.